2010
DOI: 10.1016/j.virol.2009.11.015
|View full text |Cite
|
Sign up to set email alerts
|

The Tobacco etch virus P3 protein forms mobile inclusions via the early secretory pathway and traffics along actin microfilaments

Abstract: Plant potyviruses encode two membrane proteins, 6K and P3. The 6K protein has been shown to induce virus replication vesicles. However, the function of P3 remains unclear. In this study, subcellular localization of the Tobacco etch virus (TEV) P3 protein was investigated in Nicotiana benthamiana leaf cells. The TEV P3 protein localized on the endoplasmic reticulum (ER) membrane and formed punctate inclusions in association with the Golgi apparatus. The trafficking of P3 to the Golgi was mediated by the early s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
66
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 68 publications
6
66
0
2
Order By: Relevance
“…Functional P3 protein was found to be recruited to the potyvirus replication complex (31) and to be involved in accumulation of the virus (32,33), symptomatology (34,35), viral microtubule-related inter-and intracellular movement (36), and determination of host range (33). Few examples of interaction of P3 with host factors have been reported.…”
mentioning
confidence: 99%
“…Functional P3 protein was found to be recruited to the potyvirus replication complex (31) and to be involved in accumulation of the virus (32,33), symptomatology (34,35), viral microtubule-related inter-and intracellular movement (36), and determination of host range (33). Few examples of interaction of P3 with host factors have been reported.…”
mentioning
confidence: 99%
“…Recent experiments showed that P3 is targeted to the membranes of the endoplasmic reticulum (ER) and forms inclusions associated with the Golgi apparatus that traffi c along the actin fi laments and colocalize with replication vesicles (Revers and Garcia, 2015). Two hydrophobic regions were identifi ed in the P3 of several potyviruses, and the one located in the C-terminal end of the protein was shown to be responsible for the ER targeting of P3 (Cui et al, 2010). Th is transmembrane domain is predicted to be located between residues 261 and 281.…”
Section: Genome Sequence Propertiesmentioning
confidence: 99%
“…Several viral proteins relevant to viral cell-to-cell movement hijack the actomyosin cytoskeleton to be targeted to plasmodesmata (11)(12)(13). In addition, a number of proteins and protein complexes not directly involved in cell-tocell movement have been shown to form motile inclusions and to traffic rapidly along the actin/ER network (14)(15)(16)(17)(18)(19)(20). One explanation for the motility of viral proteins is that they are anchored to, or in some cases vesiculated by, the endomembrane for the direct use of myosin motors, which provide the motive force (21,22).…”
mentioning
confidence: 99%